2012
DOI: 10.1016/j.jcrs.2011.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of steep meridian incision on corneal astigmatism in phacoemulsification cataract surgery

Abstract: Choosing the corneal incision based on the preoperative steep meridian significantly decreased keratometric astigmatism at the temporal, superotemporal, and superior locations. Thus, it is desirable to place the corneal incision on the steep meridian in eyes with corneal astigmatism higher than 0.50 D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 12 publications
6
32
0
4
Order By: Relevance
“…Studies on this subject are divided into two categories: studies which only demonstrated the results of cataract surgery with on-axis incisions and studies that compared this method with other methods. In a study of 95 eyes with on-axis incisions, Rho and Joo [21] found significant changes in the three superior, superotemporal, and temporal groups, but the greatest change was observed with the superior approach; the recommended incision site in this study for corneal astigmatism over half a diopter was the steep meridian. Altan-Yaycioglu et al [46] showed that cataract surgery performed at the steep meridian for patients with more than 0.75 D corneal astigmatism has the least changes with temporal incisions, and SIA was higher with nasal incisions.…”
Section: On-axis Incisions (Steep Axis Incision)mentioning
confidence: 46%
See 2 more Smart Citations
“…Studies on this subject are divided into two categories: studies which only demonstrated the results of cataract surgery with on-axis incisions and studies that compared this method with other methods. In a study of 95 eyes with on-axis incisions, Rho and Joo [21] found significant changes in the three superior, superotemporal, and temporal groups, but the greatest change was observed with the superior approach; the recommended incision site in this study for corneal astigmatism over half a diopter was the steep meridian. Altan-Yaycioglu et al [46] showed that cataract surgery performed at the steep meridian for patients with more than 0.75 D corneal astigmatism has the least changes with temporal incisions, and SIA was higher with nasal incisions.…”
Section: On-axis Incisions (Steep Axis Incision)mentioning
confidence: 46%
“…Factors affecting astigmatism and SIA in cataract surgery include the type, length, and location of incision and suturing techniques [12 && ,13 && , [14][15][16][17][18][19][20][21][22][23][24][25]. Thus, different incision sites (on-axis, superior, superonasal, superotemporal, and temporal), limbal relaxing incisions (LRI), and toric intraocular lenses (IOL) are astigmatism correction strategies in cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that superior corneal incisions induce greater corneal astigmatic change than temporal incisions. 9,10 Overall results from a study by Rho and Joo showed the surgically induced astigmatism (SIA) centroid (or summated vector mean) was 0.46 D at 92°in the superior incision group and 0.28 D at 79°in the temporal incision group. 10 Although the power of these vectors suggests less SIA for temporal incisions, the axes of the SIA are both near vertical.…”
Section: Placement Of Incisionsmentioning
confidence: 99%
“…9,10 Overall results from a study by Rho and Joo showed the surgically induced astigmatism (SIA) centroid (or summated vector mean) was 0.46 D at 92°in the superior incision group and 0.28 D at 79°in the temporal incision group. 10 Although the power of these vectors suggests less SIA for temporal incisions, the axes of the SIA are both near vertical. This is intuitively correct for temporal incisions (SIA being expressed, by con-vention, as a steepening effect) but appears anomolous for superior incisions.…”
Section: Placement Of Incisionsmentioning
confidence: 99%